Teacher and Parent Perceptions of Student's Learning Loss in Post-Pandemic Science Learning - Azrul Hamidi; Jumadi Jumadi; Sabar Nurohman; Andika Febrian (Postgraduate, University of Mataram, 2023)
This study aims to see how teachers and parents perceive learning loss of students after the pandemic, especially in junior high school science lessons. The research method uses a qualitative approach with the qualitative data analysis model used is Miles and Huberman, includes data collection, data reduction, data display, and conclusion. The study result that students have started to forget the atmosphere of brave learning, but habits such as wanting to easily get lesson results are still carried over to this day. Parents also feel that their children have revived their interest, motivation and learning outcomes when compared to the pandemic two years ago. The existence of online learning has an impact on learning, especially interest, motivation, and student learning outcomes. This impact has even caused learning loss for students until after the pandemic. Although slowly but surely, students' interest and learning motivation began to show an increase in line with the return to normal face-to-face learning.